Coronary bifurcation bench test using multimodality imaging: Impact of stent strut link location on stent deformity and jailed side‐branch orifices during re‐proximal optimizing technique. Issue 1 (23rd September 2018) - Kume, Teruyoshi; Yamada, Ryotaro; Koyama, Terumasa; Tamada, Tomoko; Imai, Koichiro; Fukuhara, Kenzo; Goryo, Yutaka; Kawamura, Ai; Okamoto, Hiroshi; Neishi, Yoji; Uemura, Shiro
Abstract: Objectives: The purpose of this study was to compare the stent deformation, obstruction of stent struts at a jailed side branch (SB) ostium, and stent strut malapposition after a repetitive proximal optimizing technique (re‐POT) sequence between bifurcation lesions with and without stent links at SB ostia in ex vivo experimental setting. Methods: A flexible urethane coronary bifurcation bench model was used, and crossover single stent implantation was performed from main branch (MB) with re‐POT sequence. Under videoscope observation, presence (link group, n  = 12) or absence (no‐link group, n  = 12) of stent link at distal semicircle of SB ostium was intentionally set, and rewiring was performed through distal cell in four different stent platforms. Results: There were no significant differences in the rate of malapposed struts and in SB jailing ratio after the re‐POT sequence between the link and no‐link groups. SB jailing ratio increased significantly from 8.0% to 9.6% during the second POT procedure ( P  < 0.001). SB jailing ratio after the second POT procedure differed among stent platforms. Conclusions: The presence of a stent link at an SB ostium was not associated with a rate of malapposed struts and SB jailing ratio after the re‐POT sequence. SB jailing ratio was significantly increased after second POT procedure, but was different among stent platforms. The Xience stent might minimize the change of SB jailing ratio and be suitable for coronary bifurcation stenting using re‐POT sequence.